High-resolution measurements of sediment fluxes, turbidity, and bed-level changes using SediMeter and sediment traps in Admiral Marina, Port Dickson, Malaysia (December 13, 2011–January 11, 2012, configuration 2) - Lin, Chin Yik; Lam, Su Shiung; Er, Jenn Wei; Lee, Wah Sza; Jia Hui, Ang; Erlingsson, Ulf; Gan, Yew Sun; Yee, Woei Shyan (In: Lin, CY et al. (2025): Utilizing optical backscatter sensor and sediment traps for measuring sediment dynamics in low energy marine environment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984064, 2025)
This dataset provides sediment fluxes, sedimentation rates, turbidity, and bed elevation from two deployments conducted between December 13, 2011, and January 11, 2012, in Admiral Marina, Port Dickson. The SediMeter (SM) instruments were deployed in different configurations to capture sediment dynamics during varying meteorological conditions, including a notable storm event on December 13, 2011, with rainfall of 15.3 mm, wind speeds of 9 knots, and wave heights of up to 1 meter. The highest turbidity recorded during this event was 1340.31 ± 2664.75 FBU, correlating to elevated sedimentation rates of approximately 1.175 mm/day. Subsequent periods showed net sediment erosion events, highlighting dynamic sediment resuspension processes in response to changing physical forces. Sediment traps concurrently captured sediment accumulation, enabling cross-validation of sediment influx measurements. This dataset provides valuable insights into sediment transport processes in response to episodic meteorological disturbances.
Keywords: marina; sedimentation rate; sediment fluxes; Sediment trap; SediMeter; turbidity